La "Regula" di Columba: pro-memoria per eremiti o statuto comunitario? - Grazia, Michele (Annali di storia dell'esegesi, 2000)
The "Regula", traditionally attributed to Columba of Iona, is a monastic study of Irish origin and uncertain date (the end of the fifth century to the second half of the eighth), composed of 29 simple paragraphs of varying length. Written in ancient Irish, it is a real "vademecum" for those monks, who, either from choice or force of circumstances, had withdrawn into the life of the hermitage. Through it, and because of its numerous connections with other contemporary texts of rules and penitence that also draw upon it, we can gain insight into the regime of holiness and poverty in which the Celtic anchorites passed their lives.